2015
DOI: 10.1038/modpathol.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the IASLC/ATS/ERS histological subtyping of stage I lung adenocarcinoma on intraoperative frozen sections

Abstract: Histological subtyping of surgically resected lung adenocarcinoma has been shown to be of prognostic significance, and limited surgical resection has been proposed as a treatment of choice for early-stage lung adenocarcinoma. The accuracy of histological subtyping has been recently assessed in the surgical resection and small biopsy specimens; however, the accuracy of intraoperative subtyping on frozen sections remains relatively unknown. The aim of this study was to determine diagnostic accuracy and interobse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…showed discrepancies between patterns in intraoperative frozen and permanent sections and attributed it to inadequate sampling and poor quality of frozen sections. [ 42 ] Moreover, there are no publications which have correlated biopsy patterns with patterns in the resected specimens.…”
Section: Discussionmentioning
confidence: 99%
“…showed discrepancies between patterns in intraoperative frozen and permanent sections and attributed it to inadequate sampling and poor quality of frozen sections. [ 42 ] Moreover, there are no publications which have correlated biopsy patterns with patterns in the resected specimens.…”
Section: Discussionmentioning
confidence: 99%
“… 102 Trejo et al have also reported a lower consistency between intraoperative frozen sections and permanent sections in MPA compared with other histological patterns in stage I lung ADC. 103 Therefore, at present, permanent sections, as a postoperative diagnosis, are the only reliable method to identify the presence of MPP, rather than preoperative imaging, small biopsies, and cytology or frozen sections during an operation. 31 , 104 …”
Section: Therapeutic Impactsmentioning
confidence: 99%
“…On the other hand, precise histologic subtyping, in particular detection of high grade histology is generally challenging to date. Errors in sampling and/or interpretation have been reported as major causes of frozen section misdiagnosis as lung ADC usually consists of multiple histologic subtypes . In addition, even a small amount of high‐grade histology should be detected because it contributes to an unfavorable prognosis after sublobar resection as above .…”
Section: Introductionmentioning
confidence: 99%
“…On frozen section slides, alveolar spaces are frequently collapsed, which can cause difficulty in evaluating invasion . Bittar et al . reported that the concordance rate was unsatisfactory mainly due to sampling errors and poor frozen section quality.…”
Section: Introductionmentioning
confidence: 99%